Effector T-cells are expanded in systemic lupus erythematosus patients with high disease activity and damage indexes. (January 2018) - Piantoni, S; Regola, F; Zanola, A; Andreoli, L; Dall'Ara, F; Tincani, A; Airo', P
Background and objectives: T-cell activation may be one of the pathogenic mechanisms of systemic lupus erythematosus (SLE). After repeated antigenic stimulation, T-cells undergo different modifications, leading to the differentiation into effector memory T-cells (CCR7−CD45RA−) and terminally differentiated effector memory (TDEM) T-cells (CCR7−CD45RA+). Similarly, down-modulation of CD28 may lead to the expansion of the CD28− T-cells, a subpopulation with peculiar effector activities. The aim of this study was the characterization of T-cell phenotype in a cohort of patients with SLE according to disease activity and damage index. Materials and methods: Phenotypic analysis of peripheral blood T lymphocytes of 51 SLE patients and 21 healthy controls was done by flow-cytometry. SLE disease activity was evaluated by SLE Disease Activity Index-2000 (SLEDAI-2K) and damage by the Systemic Lupus International Collaborating Clinics/American College of Rheumatology damage index (SDI). The variations between different groups were evaluated by Mann–Whitney test. Bonferroni correction was applied to adjust for multiple comparisons ( p adj ). Spearman rank test was used to evaluate the correlations between quantitative variables. Results: CD4+ lymphopenia was found among SLE patients. Patients showed a trend for a higher percentage of TDEM among the CD4+ T-cell subpopulation in comparison with healthy controls ( p = .04). SLE patients were divided into two groups according to disease activity: patients with SLEDAI-2K ≥ 6 ( n = 13) had a higher percentage of circulating CD4+ T-cells with CD28− phenotype ( p adj = .005) as well as those with an effector memory ( p adj = .004) and TDEM ( p adj = .002) phenotype and a trend of decrease of regulatory T-cells (TREGs) ( p = .02), in comparison with patients with low disease activity ( n = 38). Patients with damage (SDI ≥ 1) tended to show an expansion of TDEM among CD4+ T-cells as compared with patients with no damage ( p = .01). In SLE patients an inverse correlation was found between the percentages of TREGs and those of TDEM ( p < .01) or CD4 + CD28− ( p < .01) T-cells. Conclusions: CD4+ T-cell subpopulations displaying phenotype characteristics of effector lymphocytes are proportionally expanded in patients with active SLE and a higher damage index. These findings may suggest a role of effector T-cells in the pathogenesis of the disease and in the mechanisms of damage in SLE.